Association of Self-Perceived Health with Social and Psychological Environment, the Mode of Life and Cardiovascular Risk Markers in Middle-Aged Men – Residents of Moscow - M. B. Kotova; V. B. Rozanov; E. I. Ivanova (Рациональная фармакотерапия в кардиологии)
Aim. Estimation of the correlation of self-perceived health (SPH) with social and psychological environment, lifestyle and cardiovascular risk markers in middle-aged men.Material and methods. A total of 301 men aged 41-44 years were examined. The study included clinical examination and interrogation using a standard form. Physical activity was estimated with the help of the International Physical Activity Questionnaires, the level of psychosocial stress – with the Reeder scale, signs of vital exhaustion with the Maastricht Questionnaire Vital Exhaustion Scale. To evaluate the mode and quality of life the questionnaire developed by I.A. Gundarev was used. All the examined people were divided in three groups according to the distribution of SPH rates by tertiles: the group 1 (from 7 to 60 scores) – bad health, the group 2 (61-79 scores) – satisfactory and the group 3 (80-100 scores) – good health.Results. Parameters of the social and psychological environment of middle-aged men were the basic determinates of their health self-perception, at that majority of the indices of the quality and mode of life were independent of family material well-being. Bad SPH in middle-aged men was determined by such parameters as: increased blood pressure (BP), abdominal obesity, excessive alcohol consumption, psychosocial stress, vital exhaustion, low physical activity. Material wealth influenced systolic BP level, the waist/hips circumference ratio, a number of cigarettes per day and thus the SPH status. The most significant determinants of SPH were the level of personal happiness, nervous stress at work, support by family, sports activities, working conditions, total cholesterol level, satisfaction with own work.Conclusion. When working on programs focused on public health improvement the social, psychological and behavioral determinants of health selfperception must be considered.